STRATEGI DAKWAH SYAIKH ABDUL MALIK DALAM ISLAMISASI DI BANYUMAS (1881-1980 M) - Siti Fazriyah; Tri Rahma Hidayanti; Fatimah Zuhrotunnisa; Azaria Maulida Apriliani (STAI DI AL-HIKMAH, 2026)
The Islamization of Banyumas during the period 1881–1980 CE took place within a socio-cultural context strongly influenced by local traditions and diverse belief systems. This condition required a da’wah strategy capable of harmonizing Islamic values with local cultural practices in a peaceful and sustainable manner. This study aims to analyze the da’wah strategies employed by Syaikh Abdul Malik in the Islamization process of Banyumas and to identify the factors contributing to the success of his mission. This research adopts a qualitative library research approach. Data were collected through an extensive review of books, scholarly articles, theses, and relevant historical sources. The analysis is grounded in da’wah communication theory, which emphasizes the relationship between the preacher, da’wah messages, methods, media, and the socio-cultural conditions of the audience. The findings reveal that Syaikh Abdul Malik implemented his da’wah through the strengthening of Islamic educational institutions, the development of socio-religious networks, the utilization of oral communication and exemplary conduct, socio-economic empowerment programs, and the integration of Sufi teachings with Islamic law. These strategies significantly enhanced public acceptance of Islam, strengthened Islamic identity, and promoted socio-cultural transformation while preserving the local wisdom of Banyumas. This study concludes that the success of Islamization in Banyumas was determined not only by the dissemination of Islamic teachings but also by the ability to adapt da’wah approaches to the social and cultural characteristics of the community.